2016
DOI: 10.1021/acs.biomac.6b01392
|View full text |Cite
|
Sign up to set email alerts
|

The Label Matters: μPET Imaging of the Biodistribution of Low Molar Mass 89Zr and 18F-Labeled Poly(2-ethyl-2-oxazoline)

Abstract: Poly(2-alkyl-2-oxazoline)s (PAOx) have received increasing interest for biomedical applications. Therefore, it is of fundamental importance to gain an in-depth understanding of the biodistribution profile of PAOx. We report the biodistribution of poly(2-ethyl-2-oxazoline) (PEtOx) with a molar mass of 5 kDa radiolabeled with PET isotopes Zr andF. F-labeled PEtOx is prepared by the strain-promoted azide-alkyne cycloaddition (SPAAC) of [F]fluoroethylazide to bicyclo[6.1.0]non-4-yne (BCN)-functionalized PEtOx as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Clearly the same chemistry could be used to create hydrogels with only slight modifications. Likewise, strain‐promoted azide–alkyne cycloaddition is an example of a conjugation tool that has been adapted to create PEG hydrogels and could equally be applied to PAOx with only minor modifications to the previously reported bicyclo[6.1.0]non‐4‐yne terminated PEtOx . Similarly, glyco–PAOx, POxylated–proteins, and PAOx–nucleic acids conjugates that were previously reported have potential to be modified for hydrogel synthesis using physical or covalent cross‐linking.…”
Section: Future Directionsmentioning
confidence: 99%
“…Clearly the same chemistry could be used to create hydrogels with only slight modifications. Likewise, strain‐promoted azide–alkyne cycloaddition is an example of a conjugation tool that has been adapted to create PEG hydrogels and could equally be applied to PAOx with only minor modifications to the previously reported bicyclo[6.1.0]non‐4‐yne terminated PEtOx . Similarly, glyco–PAOx, POxylated–proteins, and PAOx–nucleic acids conjugates that were previously reported have potential to be modified for hydrogel synthesis using physical or covalent cross‐linking.…”
Section: Future Directionsmentioning
confidence: 99%
“…Wyffels and Hoogenboom introduced the preparation of high molar mass POx with molar masses up to 110 kDa and low dispersities (Đ < 1.11). [30b] In this study, PEtOx (40 kDa) was reported to be an ideal candidate which shows an optimal balance between extended blood circulation time and low non‐specific agglomeration in the body. Moreadith, Viegas and colleagues designed a polymer‐peptide conjugate based on PEtOx and rotigotine for the treatment of Parkinson's disease .…”
Section: Poly(cyclic Imino Ether)s (Poly(cie)s) Via Cationic Ring‐opementioning
confidence: 99%
“…Poly(2-oxazoline)s (POx) represent a promising alternative as they are biocompatible, [ 13 , 23 , 24 ] and show a stealth behavior similar to PEG when the side chain substitution is chosen correctly [ 25 , 26 ]. Recent studies elucidate the pharmacokinetic behavior of the polymer dependent on its molar mass, demonstrating superior behavior when compared to PEG [ 27 , 28 ]. The first clinical study using a POx derivative is currently ongoing (SER-214, phase I) [ 14 ] and the polymer was approved by the federal food administration (FDA) as an indirect additive used in food contact substances (21CFR175.105) in 2016.…”
Section: Introductionmentioning
confidence: 99%